Feministička književna kritika i hrvatska drama: izazov tradiciji? - Feminist Scholarship and the Croatian Theatre: a Challenge to Tradition? - Čale-Feldman, Lada (1999)
Članak pokazuje kako se u hrvatskoj drami 20 st. žensko tijelo nerijetko asocira uz politički kodirane koncepte nacionalne i egzistencijalne slobode, ideološke subverzije i kazališne pobune, te se suprotstavlja opsesivnoj, opresivnoj i intruzivnoj muškoj kulturi. Tako se preokupacije četvorice poetički oglednih hrvatskih dramatičara 20 st. (Vojnović, Marinković, Šnajder, Pavličić) pokazuju sukladnima stožernim kritičkim topoima suvremene feminističke teorije. This is an analysis of the uses of femaleness in the Croatian 20th century drama, which has insistently focused on female body as a metonimic sign of lost "naturalness" versus male "culturality" as sophisticated but at the same time obsessive, oppressive, and intrusive. This dichotomy, however, hides an ideologically inscribed symbolization of the female body that associates it with culturally coded concepts of existential and national freedom, ideological subversion, and theatrical revolt.
Projekt MZOS
HRV